2021
DOI: 10.3389/fped.2021.812057
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in 28-Week Triplets Caused by Intrauterine Transmission of SARS-CoV-2—Case Report

Abstract: Since the beginning of the COVID-19 pandemic, in-utero transmission of SARS-CoV-2 remains a rarity and only very few cases have been proven across the world. Here we depict the clinical, laboratory and radiologic findings of preterm triplets born at 28 6/7 weeks to a mother who contracted COVID-19 just 1 week before delivery. The triplets showed SARS-CoV-2 positivity right after birth, developed significant leukopenia and early-onset pulmonary interstitial emphysema. The most severely affected triplet I requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 41 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Six research articles [11][12][13][14][15][16] reported between 76 babies that were born from mothers infected with COVID-19, 10 babies among them were found infected with COVID-19 (10.5%), the diagnosis of COVID-19 in pregnant women and infants was based on RT-PCR, which proves that even though the placenta has ACE2 receptors does not cause the baby to be directly infected, this may be related to the function of the placenta which has physical and immunological defense functions as a barrier, and the presence of decidual macrophages for antimicrobial function, as well as placental T cells for regulation of maternal-fetal tolerance and virus-specific CD8+T cells. The decidua protects the fetus from infection, while the syncytiotrophoblast and cytotrophoblast in the placenta act as an additional barrier to the passage of infection and exhibit varying resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Six research articles [11][12][13][14][15][16] reported between 76 babies that were born from mothers infected with COVID-19, 10 babies among them were found infected with COVID-19 (10.5%), the diagnosis of COVID-19 in pregnant women and infants was based on RT-PCR, which proves that even though the placenta has ACE2 receptors does not cause the baby to be directly infected, this may be related to the function of the placenta which has physical and immunological defense functions as a barrier, and the presence of decidual macrophages for antimicrobial function, as well as placental T cells for regulation of maternal-fetal tolerance and virus-specific CD8+T cells. The decidua protects the fetus from infection, while the syncytiotrophoblast and cytotrophoblast in the placenta act as an additional barrier to the passage of infection and exhibit varying resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ACE2 receptors in 72 placenta samples combined from six research articles [11][12][13][14][15][16] by pregnant women infected with COVID-19 was found in the syncytiotrophoblast (100%), cytotrophoblast (56.9%), extravillous trophoblast (33.3%), decidual cells (2.7%), villous stromal cells (1.3%), and stromal cells (1.3%) from the placenta, this is in line with the evidence of the presence of ACE2 receptors in the placenta at the maternal-fetal interface including parts of the syncytiotrophoblast, cytotrophoblast, decidual perivascular cells, and stromal cells. 20 In Colson et al 11 study, ACE2 receptor expression was found to be quite high in syncytiotrophoblasts at <30 weeks' gestation and decreased >30 weeks' by histological score (H-score), it was also found in Zhao et al 16 Study that ACE2 receptor expression was high in early pregnancy, the different findings on ACE2 receptor expression because ACE2 receptors tend to be found to be high in early gestation, but relatively low ACE2 receptors in pregnant women with COVID-19 are associated with premature placentas and severe infections, thus, the placenta not only expresses ACE2 receptors as a portal of entry for the virus, but is also responsive to infection and results in downregulation which is an indication of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations